The Effect of Sucking Ice Cubes on Reducing Thirst in CKD Patients at Sentra Medika Cisalak Hospital - Evriana Tri Astuti; Lidia Ardani; Beatrix Elizabeth (Lembaga Pengembangan Kinerja Dosen, 2025)
Chronic kidney disease (CKD) can be defined as an irreversible impairment of kidney function, where the kidneys' ability to regulate electrolytes, fluid balance, and metabolism declines, resulting in uremia. Fluid restriction in patients with chronic kidney disease increases the frequency of thirst. The increase in plasma sodium concentration causes intracellular dehydration in the thirst center, thereby stimulating the sensation of thirst.This study aims to determine the effect of sucking ice cubes on thirst in chronic kidney disease patients at Sentra Medika Cisalak Hospital. This study uses a one-group pre-post test design. The population was taken using total sampling of 72 patients with chronic kidney disease who received the intervention of sucking ice cubes to reduce thirst. The data collected were thirst scale data before and after sucking on ice cubes. The bivariate analysis conducted was using the paired sample t-test. From the research findings, it can be concluded that there is a significant influence between sucking ice cubes and the thirst scale in patients with chronic kidney disease with p= 0.000. Conclusion sucking on ice cubes can reduce thirst in patients with chronic kidney disease.